Diboron reagents in the deoxygenation of nitrones. Issue 4 (4th January 2023) - Vargas, Emily L.; Franco, Mario; Alonso, Inés; Tortosa, Mariola; Belén Cid, M.
Abstract : B2 nep2 efficiently cleaves the N–O bond of nitrones through a concerted mechanism to form imines in very high yields via a simple, efficient and scalable protocol. Typical radical traps like DMPO and TEMPO are also deoxygenated by diboron reagents. Abstract : B2 nep2 efficiently promotes the N–O cleavage of nitrones to form imines in very high yields via a simple, efficient, sustainable, functional group tolerant and scalable protocol. The reaction occurs in the absence of additives through a concerted mechanism. We demonstrated that DMPO and TEMPO, typically used as radical traps, are also deoxygenated by diboron reagents, which demonstrates their limitation as mechanistic probes.